Association between oxidative balance score in adults with and without chronic kidney disease: 2011–2028 NHANES - Cao, Yuyu; Zhou, Yishan; Zhong, Yanghong; Liao, Xianyong; Chen, Xushan; Pi, Ying (Frontiers in Nutrition, 2024)
Oxidative stress status is associated with CKD; however, few studies have investigated this association. The oxidative balance score (OBS) reflects systemic stress status and consists of 16 anti-and pro-oxidant dietary factors and four anti-and pro-oxidant lifestyle factors. Higher OBS implies exposure to more antioxidants. The purpose of this study was to explore the association between OBS and CKD.We enrolled 8,134 study participants from the 2011-2018 National Health and Nutrition Examination Survey and obtained OBS by adding the 20 dietary and lifestyle factors. Based on OBS, the participants were divided into three groups. We performed logistic regression, subgroup analyses, and restricted cubic spline regression to explore the association between OBS and CKD. In addition, we tested the adjusted model.OBS was negatively associated with CKD (OR: 0.54; 0.66, 0.82). After adjusting for all confounders, when dietary OBS was > 20, the prevalence of CKD was reduced by 42% for each unit increase in OBS (P < 0.05). The negative associations of total OBS, dietary OBS, and lifestyle OBS with CKD were more significant in the female group. When the total OBS was 20, the trend of decreasing prevalence in the female group was more significant.OBS is negatively associated with chronic kidney disease.